2005
DOI: 10.1083/jcb.200504082
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Apaf-1 levels in cardiomyocytes engage strict regulation of apoptosis by endogenous XIAP

Abstract: Overexpression studies have identified X-linked inhibitor of apoptosis protein (XIAP) as a potent inhibitor of caspases. However, the exact function of endogenous XIAP in regulating mammalian apoptosis is less clear. Endogenous XIAP strictly regulates cytochrome c–dependent caspase activation in sympathetic neurons but not in many mitotic cells. We report that postmitotic cardiomyocytes, unlike fibroblasts, are remarkably resistant to cytosolic microinjection of cytochrome c. The cardiomyocyte resistance to cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 32 publications
5
80
2
Order By: Relevance
“…In contrast, the likelihood of MOMP induction following apoptosis stimuli seems to be unaffected by differentiation, or even higher than in undifferentiated cells [40,46,48]. Moreover, as also outline above, MOMP may be induced by elevated FAS signaling after DOX.…”
Section: Does Dox-induced Momp Render Functionally Impaired Cardiomyomentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, the likelihood of MOMP induction following apoptosis stimuli seems to be unaffected by differentiation, or even higher than in undifferentiated cells [40,46,48]. Moreover, as also outline above, MOMP may be induced by elevated FAS signaling after DOX.…”
Section: Does Dox-induced Momp Render Functionally Impaired Cardiomyomentioning
confidence: 84%
“…As such example, the studies of Potts [46] and Konorev [40] agreed that post-MOMP apoptosis is markedly reduced upon cell maturation, but attributed this effect to different protein regulation patterns. We therefore propose computational signal transduction models to investigate the effect of how combined changes in protein expression levels translate to cardiomyocyte vulnerability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ER, endoplasmic reticulum; GAB1, GRB2-associated binding protein 1; GRB2, growth factor receptorbound protein 2; NRG1, neuregulin 1; PIP 3 , phosphatidylinositol trisphosphate; SOS, son of sevenless. Unlike most tissues, neurons and cardiomyocytes are relatively resistant to apoptosis induced by cytochrome c release and caspase activation, possibly owing to increased expression of X-linked inhibitor of apoptosis (XIAP) and decreased expression of apoptotic protease activating factor 1 (APAF1) 38 . Consequently, antibodymediated inhibition of ERBB2 might regulate mitochondrial integrity through the BCL-X proteins, leading to ATP depletion and contractile dysfunction without profound changes in cardiomyocyte ultrastructure.…”
Section: Box 1 | Haematological Cancers: Good Targets For Tyrosine Kimentioning
confidence: 99%
“…X-linked inhibitor of apoptosis protein (XIAP) is the best characterized and most potent endogenous regulators of apoptotic cell death in mammals (Holcik et al 2001). Many results revealed that it was a major inhibitor of apoptosis in cardiomyocytes (Potts et al 2005;Souktani et al 2009). Our primary results found decreased cardiac expression of XIAP in aging rats, and Li et al found a downregulated XIAP expression in aging transgenic mice hearts (Li and Ren 2007).…”
Section: Introductionmentioning
confidence: 99%